2006
DOI: 10.1128/jcm.02211-05
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Analysis of Nose and Groin Swab Specimens by the IDI-MRSA PCR Assay Is Comparable to Analysis by Individual-Specimen PCR and Routine Culture Assays for Detection of Colonization by Methicillin-Resistant Staphylococcus aureus

Abstract: The IDI-MRSA assay (Infectio Diagnostic, Inc., Sainte-Foy, Quebec, Canada) with the Smart Cycler II rapid DNA amplification system (Cepheid, Sunnyvale, CA) appears to be sensitive and specific for the rapid detection of nasal colonization by methicillin-resistant Staphylococcus aureus (MRSA). We assessed the sensitivity and specificity of this assay under conditions in which both the nose and cutaneous groin specimens were analyzed together and compared the accuracy of this PCR approach to that when these spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
48
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 20 publications
7
48
3
Order By: Relevance
“…This may be explained by the use of enrichment broth as the reference method, which yields conceivably a higher sensitivity than does direct plating (17,20,23). Overall sensitivity of PCR for all swabs (n ϭ 1,595) in Amies agar corresponds well to the results reported previously using Stuart's medium (sensitivity ranging from 81% to 92.3%) (3,8,19,22,26). However, a direct comparison of Amies agar with Stuart's medium for the same clinical specimens has not been undertaken yet.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…This may be explained by the use of enrichment broth as the reference method, which yields conceivably a higher sensitivity than does direct plating (17,20,23). Overall sensitivity of PCR for all swabs (n ϭ 1,595) in Amies agar corresponds well to the results reported previously using Stuart's medium (sensitivity ranging from 81% to 92.3%) (3,8,19,22,26). However, a direct comparison of Amies agar with Stuart's medium for the same clinical specimens has not been undertaken yet.…”
supporting
confidence: 75%
“…In contrast to former PCR procedures, which required previous isolation of the organism via culture (21), the commercial BD GeneOhm MRSA assay (formerly IDI-MRSA; BD-GeneOhm, San Diego, CA) discriminates mecA-positive Staphylococcus aureus from coagulase-negative staphylococci (CoNS) and detects MRSA in clinical specimens within a few hours. This real-time PCR assay has been used particularly in high-prevalence areas (3,6,9). In Switzerland, MRSA prevalence ranges between 4 and 7% with the exception of Geneva (Ͼ25% [4,14]).…”
mentioning
confidence: 99%
“…Previous evaluations of the IDI-MRSA kit quoted sensitivity values of 92%-100% but comparisons were made against direct culture on MSA and, when enrichment culture was used, subcultures were made onto BA [15,16]. More recently, sensitivities of 89% with nasal specimens and 82% with groin specimens were reported when comparison was made a Direct and enrichment culture results b Amended results: see footnote to Table 3 Table 4 Sensitivity, specificity and positive (PPV) and negative (NPV) predictive values expressed as a percentage for the IDI-MRSA kit compared with culture from nose, throat and groin/perineum specimens (numbers in parentheses 95% confidence intervals, All, PPP all sites from previously positive patients, All, NPP all sites from patients with no record of being previously positive) against direct and enrichment culture on MSA containing oxacillin (OMSA) [17]. Studies comparing culture media selective for MRSA have shown that OMSA has sensitivities ranging from 60% to 84%, whereas the CA used in the present study (MRSA-Select) has a sensitivity of 97%-99% [1,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Direct comparison of the distribution of intestinal carriers versus nasal carriers amongst MRSA-colonized patient groups could be deduced from 22 reports (Table 4) [9,10,13,18,19,[22][23][24][25][26][27][28][29][31][32][33][34][35][36][37][38][39]. Table 4 surveys the frequency of patients with intestinal carriage and nasal carriage expressed as a percentage of all MRSA-colonized patients found in the various studies.…”
Section: Distribution Of Mrsa Detection Sitesmentioning
confidence: 99%